Occurrence of Thanatus atratus Simon, 1875 (Araneae: Philodromidae) in Poland - Rozwałka, Robert; Rutkowski, Tomasz; Staręga, Wojciech; Sienkiewicz, Paweł (Biological Letters, 2016)
The paper presents data on the occurrence of Thanatus atratus in Poland. The long-lasting confusion in Polish and European literature about the existence of 2 similar species T. atratus / T. vulgaris in Poland is clarified. Diagnostic images of T. atratus reproductive organs of both sexes are presented.